The antimicrobial activity of exogeno us anionic phospholipids against Mycobacterium tuberculosis and Escherichia coli - Yu. L. Mikulovich; G. M. Sorokoumova; А. А. Selishcheva; V. I. Shvets (Тонкие химические технологии, 2016)
The effect of anionic phospholipids, namely, cardiolipin, phosphatidylglycerol and phosphatidic acid, on the growth of gram-negative bacteria E. coli BL21(DE3), as well as gram-positive bacteria M. tuberculosis H37Rv was investigated in this study. The influence of all anionic phospholipids tested on the bacteria growth was shown to be dose-dependent. Lipids at concentrations below 335 μM didn’t affect, while at 335 μM and above they repressed bacteria growth and caused cellular death of both type of microorganisms. SOS response induction was observed by using strain E. coli CSH50 sfiA::lacZ during cultivation E. coli with cardiolipin, phosphatidylglycerol and phosphatidic acid. This indicates DNA damage through double-strand breaks. One reason of the DNA damage could be stabilization of transient complexes of DNA topoisomerase (types I and II) with DNA temporary broken by anionic phospholipids. However, neither phosphatidylglycerol nor phosphatidic acid affect the activity of types I and II DNA topoisomerases from E. coli in vitro. In contrast, cardiolipin inhibited DNA topoisomerase I and DNA gyrase (type II topoisomerase), but didn’t stabilize transient complexes of the enzyme with DNA. It indicates that DNA damage due to anionic phospholipids exposure didn’t result from inhibition of DNA topoisomerase activity through stabilization of the transient complex of the enzyme with DNA. The obtained results of cardiolipin, phosphatidylglycerol and phosphatidic acid bactericidal activity against grampositive M. tuberculosis and gram-negative E. coli make it possible to use anionic phospholipids as individual antimicrobial agents or as a matrix of effective and non-toxic liposomal drugs for tuberculosis treatment.